Palliative surgery versus medical management for bowel obstruction in ovarian cancer - Kucukmetin, Ali (John Wiley & Sons, Ltd, 2010)
BACKGROUND: Ovarian cancer is the sixth most common cancer among women and is usually diagnosed at an advanced stage. Bowel obstruction is a common feature of advanced or recurrent ovarian cancer. Patients with bowel obstruction are generally in poor physical condition with a limited life expectancy. Therefore, maintaining their QoL with effective symptom control is the main purpose of the management of bowel obstruction. OBJECTIVES: To compare the effectiveness and safety of palliative surgery (surgery performed to control the cancer, reduce symptoms and improve quality of life for those whose cancer is not able to be entirely removed) and medical management for bowel obstruction in women with ovarian cancer. SEARCH METHODS: We searched the Cochrane Gynaecological Cancer Group Trials Register, The Cochrane Central Register of Controlled trials (CENTRAL), Issue 1 2009, MEDLINE and EMBASE up to February 2009. We also searched registers of clinical trials, abstracts of scientific meetings, reference lists of included studies and contacted experts in the field. SELECTION CRITERIA: Studies that compared palliative surgery and medical interventions, in adult women diagnosed with ovarian cancer who had either full or partial obstruction of the bowel. Randomised controlled trials (RCTs) and non‐RCTs that used multivariable statistical adjustment for baseline case mix were eligible. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed whether potentially relevant studies met the inclusion criteria, abstracted data and assessed risk of bias. One non‐randomised study was identified so no meta‐analyses were performed. MAIN RESULTS: The search strategy identified 183 unique references of which 22 were identified as being potentially eligible on the basis of title and abstract. Only one study met our inclusion criteria and was included in the review. It analysed retrospective data for 47 women who received either palliative surgery (n = 27) or medical management with Octreotide (n = 20) and reported overall survival and perioperative mortality and morbidity. Women with poor performance status were excluded from surgery. Although six (22%) women who received surgery had serious complications of the operation and three (11%) died of complications, multivariable analysis found that women who received surgery had significantly (p < 0.001) better survival than women who received Octreotide, after adjustment for important prognostic factors. However, the magnitude of this effect was not reported. Quality of life (QoL) was not reported and adverse events were incompletely documented. AUTHORS' CONCLUSIONS: We found only low quality evidence comparing palliative surgery and medical management for bowel obstruction in ovarian cancer. Therefore we are unable to reach definite conclusions about the relative benefits and harms of the two forms of treatment, or to identify sub‐groups of women who are likely to benefit from one treatment or the other. However, there is weak evidence in support of surgical management to prolong survival.